COMPARATIVE TREATMENT OF WELL AND STREAM WAGTER FOR DRINKING USING MORINGA OLEIFERA SEEDS, ALUM, SAND FILTER BEDS AND SOLAR RADIATION - Benjamin, MOSES Ikechukwu; Babatunde, Awopetu; Odeyemi, Olu (Crosshouse books, 2020)
International Journal of Tropical Medicine and Public Health.vol. 1,No. 1, pages 9